2009
DOI: 10.1113/expphysiol.2009.050526
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species are signalling molecules for skeletal muscle adaptation

Abstract: Increased reactive oxygen species (ROS) production is crucial to the remodelling that occurs in skeletal muscle in response to both exercise training and prolonged periods of disuse. This review discusses the redox-sensitive signalling pathways that are responsible for this ROS-induced skeletal muscle adaptation. We begin with a discussion of the sites of ROS production in skeletal muscle fibres. This is followed by an overview of the putative redox-sensitive signalling pathways that promote skeletal muscle ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
282
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(301 citation statements)
references
References 69 publications
5
282
2
12
Order By: Relevance
“…(Ascensao et al, 2005;Kavazis et al, 2010). ROS can also activate signal-transduction pathways to induce a stress-resistance response that protects against some of the toxic outcomes of ROS generation (Powers et al, 2010). In contrast, exercise seems to increase the oxygen consumption rate by 10-20 fold as reported earlier and might have released the above factors and thereby induced oxidant activity (Husain, 2002).…”
Section: Discussionmentioning
confidence: 81%
“…(Ascensao et al, 2005;Kavazis et al, 2010). ROS can also activate signal-transduction pathways to induce a stress-resistance response that protects against some of the toxic outcomes of ROS generation (Powers et al, 2010). In contrast, exercise seems to increase the oxygen consumption rate by 10-20 fold as reported earlier and might have released the above factors and thereby induced oxidant activity (Husain, 2002).…”
Section: Discussionmentioning
confidence: 81%
“…Recent studies from our research group [21,39] and other groups [40][41][42] have shown the involvement of oxidative stress factors (or their end products) in skeletal muscle atrophy. Powers et al [10] presented a review on the influence of reactive oxygen and nitrogen species on the induction of three main proteolytic pathways: the calpain, caspase, and ubiquitin-proteasome pathways. Several studies have shown that these reactive species contribute to skeletal muscle dysfunction through different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms may lead to increased oxidative stress in cancer patients. Recent evidence suggests that activation of the proteolytic pathways in muscle tissue is related to increased levels of reactive oxygen species (ROS) [10]. One of the mechanisms proposed for this observation is that high ROS production leads to highly reactive aldehydes, causing dysfunction in the Ca 2+ -ATPase pump, thereby delaying the removal of cytosolic calcium and thus the activation of calcium-dependent pathways [11].…”
Section: Introductionmentioning
confidence: 99%
“…During exercise, the levels of both reactive oxygen species and reactive nitrogen species are increased (26). The production of such species is crucial for the beneficial effects of exercise (27)(28)(29) and for force development (30). However, excess production is detrimental for skeletal muscle performance (30,31).…”
mentioning
confidence: 99%